Controlled synthesis of CdE (E=S, Se and Te) nanowires - Xi, Lifei (2012)
This work focused on a catalyst-free solution-based method to synthesize single-crystal CdE (E = S, Se and Te) nanowires. Using the hot coordinating solvents method, we have successfully synthesized high aspect ratio CdE nanowires. In this paper, we present our very recent results on the synthesis of CdTe nanowires and summarize our understanding of the effect of reaction parameters on the growth of CdE nanowires. The reaction parameters include ligands for Cd-complexes and E-complexes, ligand-to-Cd mole ratio, Cd-to-E mole ratio, precursor concentration, reaction temperature and the injection process. We propose the optimum conditions for the growth of CdE nanocrystals with a large aspect ratio. Possible growth mechanisms were also investigated using time-dependent studies. Furthermore, a Raman study shows a higher concentration of tellurium on the surface of CdTe nanowires. This is understandable because the free energy of Te is smaller than that of CdTe and thus Te crystals can easily form during the synthesis. Our high aspect-ratio nanowires have good dispersibility and exhibit huge potential applications in areas such as solution processed photovoltaic cells and transistors.